Design and Validation of a Practicum Module for Gravimetric Analysis Techniques in Project-Based Learning - Khusna Arif Rakhman; Nurfatimah Sugrah; Ilham S.W. Mauraji; Sudir Umar; Agung Abadi Kiswandono (Chemistry Education Department of Education and Teaching Faculty, 2024)
Gravimetry is a simple and fast method used to determine the weight percentage of alkaloid content in natural samples when analyzing compound content. Gravimetry is a basic knowledge and skills in analytical chemistry. A student-centered learning approach is needed to acquire integrated chemical laboratory knowledge and skills. Integrated learning outcomes between knowledge and skills can be achieved, one of which is through project-based learning (PjBL). One of the things we report in this article is the development of a practical module based on PjBL. This article reported the research and development (RnD) of a project-based practical module on gravimetric analysis using the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) stages to obtain a valid and reliable practical module. The module's validation was analyzed using content validity with the FGD technique through the assessment of five experts. Validity data analysis used Aiken's and Cronbach's alpha for reliability. This article also reports the results of observations of the PjBL practicum of gravimetric alkaloid analysis by 18 students regarding the clarity of the practicum objectives, content, instructions, and ease of the module in guiding the practicum in the Laboratory. By using the ADDIE development steps, we produced a PjBL practicum module with the validity of the Aiken analysis results showing an index of 0.92, indicating that the module developed was valid, had a reliability of 0.78, and had a practicality percentage of 89.77%. The developed PjBL teaching module has also increased students' motivation and basic chemistry laboratory skills when conducting gravimetric analysis practicum.